BASE DE DATOS DE NO-PALABRAS DE CUATRO LETRAS PARA SU USO EN TAREAS EXPERIMENTALES DE DECISIÓN LÉXICA - Alameda, José Ramón (R.E.M.A. Revista electrónica de metodología aplicada, 2012)
The no-words selection is important in lexical decision task. The similarity between nowords and words determine the recognition time to no-words, when the no-words are similarity to high frequency words the response time is highter than in the opposite case. In this paper, we present a no-words base where the similar words number, the acumulative frequency from this one, and the similar words numbers by the changing letter, is shown.